2008
DOI: 10.1111/j.1365-3156.2008.02160.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐partum depression in Kinshasa, Democratic Republic of Congo: Validation of a concept using a mixed‐methods cross‐cultural approach

Abstract: Summaryobjective To determine if a post-partum depression syndrome exists among mothers in Kinshasa, Democratic Republic of Congo, by adapting and validating standard screening instruments.methods Using qualitative interviewing techniques, we interviewed a convenience sample of 80 women living in a large peri-urban community to better understand local conceptions of mental illness. We used this information to adapt two standard depression screeners, the Edinburgh Post-partum Depression Scale and the Hopkins Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 29 publications
3
73
0
1
Order By: Relevance
“…Relevant for this study, the study questionnaire included sections for symptoms of distress, functioning, and traumatic experiences as described below. All measures were adapted to the local context by using data from a previously conducted qualitative study and then translated into the five study languages (for a detailed description of the process refer to Applied Mental Health Research Group, 2013a, 2013b; Bass, Ryder, Lammers, Mukaba, & Bolton, 2008). The qualitative study consisted of free list interviews with women living in three communities with high rates of sexual violence in South Kivu and key informant interviews with men and women identified through snowball sampling from the same communities (report available upon request).…”
Section: Methodsmentioning
confidence: 99%
“…Relevant for this study, the study questionnaire included sections for symptoms of distress, functioning, and traumatic experiences as described below. All measures were adapted to the local context by using data from a previously conducted qualitative study and then translated into the five study languages (for a detailed description of the process refer to Applied Mental Health Research Group, 2013a, 2013b; Bass, Ryder, Lammers, Mukaba, & Bolton, 2008). The qualitative study consisted of free list interviews with women living in three communities with high rates of sexual violence in South Kivu and key informant interviews with men and women identified through snowball sampling from the same communities (report available upon request).…”
Section: Methodsmentioning
confidence: 99%
“…The development and testing of the FAI included two phases, described below, as suggested by Bolton and his colleagues ([5, 17]: (a) free-listing qualitative interviews to identify common tasks and activities of women during the perinatal period, in order to construct the Functional Assessment Instrument ((FAI); and (b) a validation study of the constructed instrument. Data collection was carried out in Khayelitsha, Cape Town, at the Community Health Centre where the trial is being conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Functional consequences of maternal depression have been described and noted [17, 18], but there remains a gap in methods for assessing functioning in these women. Some commonly used instruments for maternal depression do include some measures of functional status, but these do not provide a sufficiently detailed profile of functioning for these women.…”
Section: Introductionmentioning
confidence: 99%
“…108 A recent study that investigated PPD in the Democratic Republic of Congo reported that, despite the fact that Western models of psychopathology may be inappropriate for establishing diagnosis according to local tenets, a local syndrome similar to depression was observed. 109 The shortage of psychiatrists in West Africa combined with of limited screening skills of the obstetric personnel hinders the detection and effective treatment of PPD in Africa. 100 Nevertheless, a research conducted in Zimbabwe demonstrated the feasibility and effectiveness of a brief method for identifying women at high risk for developing a postnatal mental disorder.…”
Section: Postpartum Depression Screening Scale -Pdssmentioning
confidence: 99%